PENGGUNAAN MODEL NUMBERED HEADS TOGETHER (NHT) DALAM PEMBELAJARAN IPA DI KELAS V SD - khasanah, nur (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Nur Khasanah 1, Suhartono 2, Ngatman 3 1 Mahasiswa PGSD FKIP Universitas Sebelas Maret Kampus Kebumen 2 3 Dosen FKIP Universitas Sebelas Maret Kampus Kebumen Jalan Kepodang 67 A Telp (0287) 381169 Kebumen 54312 e-mail : gondallique@yahoo.co.id Abstract: The Used of Numbered Heads Together (NHT) Model On Science Learning at  The Fifth Grade of State Elementary School. The purpose of this research is to improve the learning of science learning at the fifth grade of elementary school with Numbered Heads Together (NHT) model. This research was collaborative classroom action research was conducted in two cycles and each cycle consisted of planning, implementation, observation, and reflection. The objects of this research were students at the fifth grade of elementary school. The techniques collecting data used observation, interviews, and tests. The validity of the data used triangulation. The result of this research is the use of Numbered Heads Together (NHT) learning model could improve the learning of science learning at the fifth grade state elementary school. Keywords: Numbered Heads Together (NHT), Science Learning, fifth grade   Abstrak: Penggunaan Model Numbered Heads Together (NHT) dalam Pembelajaran IPA di Kelas V SD. Tujuan penelitian ini adalah meningkatkan pembelajaran IPA di kelas V SD dengan menggunakan model pembelajaran Numbered Heads Together. Penelitian ini merupakan penelitian tindakan kelas kolaborasi yang dilaksanakan dalam dua siklus, masing-masing siklus mencakup tahap perencanaan, pelaksanaan, observasi dan refleksi. Objek penelitian ini adalah siswa kelas V SD. Teknik pengumpulan data menggunakan observasi, wawancara, dan tes. Validitas data menggunakan triangulasi sumber dan teknik. Hasil penelitian ini menunjukkan bahwa penggunaan model pembelajaran Numbered Heads Together (NHT) dapat meningkatkan pembelajaran IPA kelas V SD. Kata kunci: Numbered Heads Together (NHT), pembelajaran IPA, kelas V